1954
DOI: 10.2307/1538767
|View full text |Cite
|
Sign up to set email alerts
|

Nutrition of the Sea Urchin, Strongylocentrotus Purpuratus

Abstract: The gut of the purple sea urchin, Strongylocentrotus purpiiratus, reveals a mass of algae in various stages of decomposition. Algae contain relatively small amounts of nutrients which are readily handled by enzymes ordinarily present in animals, but they possess galactans, alginic acid, agar and possibly some cellulose, none of which are digested by man or most animals. The urchins in the course of evolution may have developed enzymes which have enabled them to use these materials, or, like many of the ungulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
64
0

Year Published

1958
1958
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 128 publications
(69 citation statements)
references
References 15 publications
(11 reference statements)
5
64
0
Order By: Relevance
“…Seasonal variation in algal composition (Lobban & Harrison 1994) and changes in dietary requirements of urchins with age (Kelly et al 1998) and season (Larson et al 1980) also may affect our estimates of fecal output of organic carbon and nitrogen during destructive grazing in each community state. There is no effect of urchin size (juveniles and adults) on absorption efficiency in S. droebachiensis (Miller & Mann 1973) or feeding frequency in conspecific species (S. purpuratus, Lasker & Giese 1954, Boolootian & Lasker 1964S. intermedius, Fuji 1967), suggesting that fecal production does not vary greatly among individuals in a grazing front, which is composed of mainly large adults (Meidel & Scheibling 1998).…”
Section: Defecation Rate and Absorption Efficiencymentioning
confidence: 99%
“…Seasonal variation in algal composition (Lobban & Harrison 1994) and changes in dietary requirements of urchins with age (Kelly et al 1998) and season (Larson et al 1980) also may affect our estimates of fecal output of organic carbon and nitrogen during destructive grazing in each community state. There is no effect of urchin size (juveniles and adults) on absorption efficiency in S. droebachiensis (Miller & Mann 1973) or feeding frequency in conspecific species (S. purpuratus, Lasker & Giese 1954, Boolootian & Lasker 1964S. intermedius, Fuji 1967), suggesting that fecal production does not vary greatly among individuals in a grazing front, which is composed of mainly large adults (Meidel & Scheibling 1998).…”
Section: Defecation Rate and Absorption Efficiencymentioning
confidence: 99%
“…The importance of this process in echinoids is still unknown, but it may be high (Miller & Mann 1973), and thus contribute to the overestimation of actual absorption rates. Second, in echinoids, absorption rates are affected by the microflora associated with the gut (Lasker & Giese 1954, Fong & Mann 1980. During long-term monospecific feeding experiment this microflora may become more and more adapted to digest the offered food.…”
Section: Absorptionmentioning
confidence: 99%
“…This dependence results from the poor musculature associated with the gut of echinoids (De Ridder & Jangoux 1982), thus enhancing the importance of water and newly ingested material in materials progressing through the gut. This explains why starving echinoids have a much longer gut residence time than continuously feeding echinoids (Lasker & Giese 1954, Bedford & Moore 1985. It is assumed that gut residence time and absorption rates of benthic primary consumers are positively correlated (Lopez & Levinton 1987).…”
Section: Absorptionmentioning
confidence: 99%
“…Fong & Mann (1980) showed that the gut microflora of a sea urchin, Strongylocentrotus droebachiensis, was capable of uptake of 14C-labelled glucose, and that the label from bacterial protein was subsequently incorporated into the tissues of the urchin. Mann (1982) also cites results of work in which 14C-label in cellulose was incorporated into bacterial protein and subsequently appeared in the proteins of the urchins (see also Lasker & Giese 1954. Prim & Lawrence 1975.…”
Section: Introductionmentioning
confidence: 99%